1998
DOI: 10.1021/cm9705202
|View full text |Cite
|
Sign up to set email alerts
|

Selective Ion-Exchange Intercalation of Isomeric Dicarboxylate Anions into the Layered Double Hydroxide [LiAl2(OH)6]Cl·H2O

Abstract: The dicarboxylate anions 1,4-benzenedicarboxylate and fumarate can be selectively intercalated into the layered double hydroxide [LiAl 2 (OH) 6 ]Cl‚H 2 O from equimolar molar mixtures of the 1,2-, 1,3-, and 1,4-benzenedicarboxylate and fumarate and maleate isomers, respectively. Time-resolved in situ energy-dispersive X-ray diffraction studies have shown that these are the thermodynamic products following the conversion of an initial phase in which all the anions are simultaneously intercalated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
122
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(124 citation statements)
references
References 20 publications
1
122
0
Order By: Relevance
“…Similar separation behavior has been reported for layered double hydroxides in the presence of a solution of carboxylate anions: when exposed to a mixture of two anions the initial rapid uptake of both takes place before the sole product containing one anion is formed with expulsion of the other. 43,44 Studies of the separation of both the gas phase and the liquid phase separation of xylene (and other aromatic) isomers by materials with the MIL-53 structure have recently been reported by other groups. For example, Alaerts et al showed that MIL-53(Al) would preferentially bind ortho-isomers of xylene, ethyltoluene, and so forth in liquid phase separations, and rationalized the selectivity as arising from strong interactions between methyl groups of the sorbates and carboxylate moieties in the pore corners.…”
Section: Resultsmentioning
confidence: 99%
“…Similar separation behavior has been reported for layered double hydroxides in the presence of a solution of carboxylate anions: when exposed to a mixture of two anions the initial rapid uptake of both takes place before the sole product containing one anion is formed with expulsion of the other. 43,44 Studies of the separation of both the gas phase and the liquid phase separation of xylene (and other aromatic) isomers by materials with the MIL-53 structure have recently been reported by other groups. For example, Alaerts et al showed that MIL-53(Al) would preferentially bind ortho-isomers of xylene, ethyltoluene, and so forth in liquid phase separations, and rationalized the selectivity as arising from strong interactions between methyl groups of the sorbates and carboxylate moieties in the pore corners.…”
Section: Resultsmentioning
confidence: 99%
“…18 LiAl 2 -Cl has also been found to preferentially intercalate 1,4-BDC over 1,2-BDC with > 95% selectivity. 17 The same preferential intercalation of 1,4-BDC occurs for the [Ca 2 Al(OH) 6 ]NO 3 $2H 2 O LDH, 19 and other LDH systems such as [MAl 4 (OH) 12 ](NO 3 ) 2 $yH 2 O (M ¼ Zn, Cu, Ni, or Co). 20 Analogous trends are observed for nitrophenols (4-nitrophenol is intercalated in preference to the 2-and 3-nitrophenol isomers).…”
Section: Introductionmentioning
confidence: 83%
“…A range of isomer mixtures have been explored by a number of scientists. For instance, fumarate is found to be intercalated preferentially over maleate into the LDH [LiAl 2 (OH) 6 ]Cl$H 2 O (LiAl 2 -Cl), 17 and also into [Mg 2 Al(OH) 6 ] Cl$1.5H 2 O. 18 LiAl 2 -Cl has also been found to preferentially intercalate 1,4-BDC over 1,2-BDC with > 95% selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to examine how the guest anions such as muconates intercalate into the interlayer of LDH accompanying the structural modification of inorganic host lattice and how it is possible to selectively separate one isomer from the various isomeric mixtures. Recently, O'Hare et al reported on the selective intercalation into the interlayer of [LiAl 2 (OH) 6 ]Cl · H 2 O and Ca 2 Al(OH) 6 · NO 3 · 2H 2 O LDHs for the ion-exchange reaction with equimolar isomeric mixtures of dicarboxylates by kinetics studies using the time-resolved in situ energy dispersive X-ray powder diffraction method (41)(42)(43)(44)(45). They suggested that the selective ion-exchange reactions involved the initial kinetic insertion of all the isomers followed by a collapse to the thermodynamically most stable intercalate phase as a result of expelling the disfavored anions.…”
Section: Introductionmentioning
confidence: 99%